Length dependent performance of Cu2O/ZnO nanorods solar cells. (February 2019) - Hussain, S.; Jacob, Jolly; Usman, Z.; Mahmood, K.; Ali, A.; Arshad, M.I.; Khan, Waheed S.; Farooq, Z.; Farooq, M.U.; Ashfaaq, A.; Rehman, U.
Abstract: Cu2 O/ZnO heterojunction is one of the potential candidates in solar cell's applications due to its non-toxic and easy fabrication process. Here we report the synthesis of ZnO nanorods (1–3 μm long) via solution method to fabricate the Cu2 O/ZnO based solar cells. Length dependent studies of the nanorods reveal lower transmission of light at an optimized length of 2 μm. Thus we find an improvement in surface charge area possibly due to the imbed Cu2 O film on ZnO nanorods and the formation of radial junction dictates enhanced photocurrent (Jsc ) and lower recombination. We further explore that the wurtzite ZnO nanorods of 3 μm length encounter reduced charge carriers density and hence relatively lower current were observed in contrast with those of optimized length. We conclude that lower fill factors and open circuit voltages for 1 μm and 3 μm long nanorods are the result of higher electron-hole pair recombination. The optimal conversion efficiency of Cu2 O/ZnO solar cell, having an optimized length of 2 μm is measured to be 0.65%. Highlights: The Cu2 O/ZnO nanorods solar cells were fabricated by using hydrothermal and electrodeposition techniques. Transmission of photons decreased with increasing in length of ZnO nanorods. The current–voltage (IV) characteristics were measured under illumination.